Histology and Ultrastructure of the Esophagus in European Beaver (Castor fiber) Displays Features Adapted to Seasonal Changes in Diet - Kamila Martyniuk; Natalia Ziółkowska; Maria Hanuszewska-Dominiak; Natalia Szyryńska; Bogdan Lewczuk (Animals, 2023)
The European beaver is a herbivorous rodent whose diet changes seasonally, and in winter consists of large quantities of woody plants. It is distinguished among other mammals by a unique organization of the stomach that comprises the cardiogastric gland and by the unusual process of mucus formation in the gastric mucosa. The aim of study was to (i) characterize the structure of the beaver esophagus with particular attention to the mucosal epithelium; (ii) compare the histological structure of the esophagi collected in spring, summer, and winter; (iii) provide preliminary data on the structure of the esophagus in beaver fetuses. The study was conducted on esophagi of 18 adult beavers captured in Poland in April, August, and December, and on 3 fetal organs. The results obtained in adults show that the mucosa is lined with thick stratified squamous keratinized epithelium with a structure similar to that of the skin epidermis. Ultrastructural studies reveal the presence of multiple lamellar and non-lamellar bodies in granular cells, whose morphology and location gradually change while reaching the upper epithelial layers. The muscularis mucosa comprises a layer of longitudinally oriented bundles of smooth muscle cells. Both mucosa and submucosa do not comprise any glands. The thick muscularis externa consists mainly of internal circular and external longitudinal layers of striated muscle fibers. The keratinized layer of mucosa epithelium was 2-3-fold thicker in esophagi collected in winter than in those collected in spring and summer, while the epithelial cell layer thickness remained unchanged regardless of the season. Immunolabeling for proliferating cell nuclear antigen shows a higher index of epithelium proliferation in esophagi collected in winter than in spring and summer. No seasonal differences were noted in other layers of the esophagus. Fetal organs have epithelium covered with a keratinized layer, thinner than in adults, and the muscularis externa comprises both striated and smooth muscle cells.